GERMAN LITERATURE REALISM OF 20th CENTURY: ON THE EXAMPLE OF THE WORKS OF HENRICH BÖLL (Journal of Universal Science Research, 2025)
The article reveals the role of the famous writer and poet, public figure Heinrich Böll, who played an important role in the development of the approach of realism in the German literature of the 20th century. In addition, the early and post-war novels of the author were analyzed in comparative way.